Adherence to Mediterranean Diet and Metabolic Syndrome in BRCA Mutation Carriers. (March 2018) - Bruno, Eleonora; Manoukian, Siranoush; Venturelli, Elisabetta; Oliverio, Andreina; Rovera, Francesca; Iula, Giovanna; Morelli, Daniele; Peissel, Bernard; Azzolini, Jacopo; Roveda, Eliana; Pasanisi, Patrizia
Background . Insulin resistance is associated with higher breast cancer (BC) penetrance in BRCA mutation carriers. Metabolic syndrome (MetS), an insulin resistance syndrome, can be reversed by adhering to the Mediterranean diet (MedDiet). In a dietary intervention trial on BRCA mutation carriers, we evaluated adherence to the MedDiet, and the association with the MetS, by analyzing data from the Mediterranean Diet Adherence Screener (MEDAS). Methods. BRCA mutation carriers, with or without BC, aged 18 to 70 years, were eligible for the trial. After the baseline examinations, women were randomized to a dietary intervention or to a control group. Both groups completed the MEDAS at baseline and at the end of the dietary intervention. Results . A total of 163 women completed the 6 months of dietary intervention. Compared with controls, the women in the intervention group significantly reduced their consumption of red meat ( P < .01) and commercial sweets ( P < .01) and their MEDAS score rose significantly (+1.3 vs +0.55, P = .02). The number of MetS parameters decreased with increasing points of adherence to the MEDAS score ( P = .01). In the intervention group, there was a significant association with the greater reduction of MetS. Conclusion. BRCA mutation carriers in the intervention group experienced greater improvement in their MedDiet and MetS parameters.